2021
DOI: 10.1016/j.enfcli.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Abordaje del duelo y de la muerte en familiares de pacientes con COVID-19: revisión narrativa

Abstract: Abordaje del duelo y de la muerte en familiares de pacientes con covid-19: revisión narrativa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
0
19
0
7
Order By: Relevance
“…Nursing staff sought ways to make up for this phenomenon with technological devices such as phones and tablets. The use of these support elements was increased in end-of-life situations ( Araujo Hernández et al, 2020 ). The psychological state of the patients, along with the emergency situation and the unknown conditions of the COVID-19 pathology, were the nurses’ main concerns ( Sun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff sought ways to make up for this phenomenon with technological devices such as phones and tablets. The use of these support elements was increased in end-of-life situations ( Araujo Hernández et al, 2020 ). The psychological state of the patients, along with the emergency situation and the unknown conditions of the COVID-19 pathology, were the nurses’ main concerns ( Sun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study carried out to determine the relationship between attitude and coping of the nurse with the death of the patient with COVID-19 in critical units, it was found that there is a weak correlation between attitude and coping of the nurse with the death of the patient with COVID-19 in critical units; accepting the alternative hypothesis. These results can be compared with the study by Araujo, García and García-Navarro (2020). Those who argue that the process of death in times of COVID19, emotionally affected health workers especially nurses who live the experience of working directly with situations of sadness and pain.…”
Section: Discussion Y Conclusionmentioning
confidence: 95%
“…Another noteworthy result, consistent with previous research, 65,66 is the association between PTSSs and having attended critical patients at T2 or patients who died of COVID-19 at T1 or T2. The exceptional circumstances that characterize this pandemic have been responsible for families being unable to accompany their loved ones who are gravely ill, and many persons have died alone 67 . This circumstance has been especially difficult for healthcare workers who have witnessed this reality, 68 and it has made their role in end-of-life care more important than ever before.…”
Section: Discussionmentioning
confidence: 99%